Where and How Slum Electrification Succeeds : A Proposal for Replication - Dave, Rutu (World Bank, Washington, DC, 2019)
Substantial gains have been made in recent years in electrifying urban and peri-urban areas in the developing world, in partial fulfillment of the global commitment to ensure access to affordable, reliable, and modern energy for all by 2030. But additional efforts are required to reach slum dwellers, who often fall back on power theft or informal connections to obtain access to electricity. This kind of access, however, comes at a high cost for paying customers and distribution companies. Joint efforts by government, utilities, and local populations can break the vicious cycle of theft and poor service.